Evaluating the Murine Anti-Human Antibody Response and Assessment of General Activity and Cognition after Treatment with Human Intravenous Immunoglobulins in Healthy Adult C57/B6J Mice. (September 2014) - Fülber, I.; Bacher, M.; Dodel, R.; Röskam, S.
Human intravenous immunoglobulin (IVIG) is a fractionated blood product that is used for the treatment of several autoimmune and immunodeficiency disorders. Recently, IVIG has been suggested for the treatment of Alzheimer's disease (AD). However, the molecular mode of action is still largely unknown. Therefore, preclinical assessment of the therapeutic efficacy of IVIG in animals may provide valuable information of the function of IVIG in vivo . However, it is recommended to determine the murine-anti-human antibody (MAHA) response in those animals before starting immunotherapy and subsequent assessment of the therapeutic efficacy in animal models for AD. After weekly administration of 400 μg IVIG in C57/B6J mice for the duration of twelve weeks, we found a significant increase of MAHA response against human IgG. Even after increased MAHA levels starting from week nine after treatment, there was no significant change in basic exploratory behavior, anxiety, and cognition. Therefore, it is suitable to study pharmacological and immunological activity, therapeutic efficacy, as well as mode of action of IVIG in animal models only for a short duration to avoid interference with IVIG treatment and neutralize possible therapeutic effects.